2006
DOI: 10.17221/3455-pse
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of mineral nitrogen from subsoil by winter wheat

Abstract: The apparent uptake of mineral nitrogen (N min ) from top-and subsoil layers during the growth of winter wheat (Triticum aestivum L.) was studied in Prague-Ruzyne on clay loam Chernozem soil in years 1996 and three treatments, unfertilized (N0), fertilized with 100 kg (N1) and 200 kg (N2) nitrogen per hectare were observed in years 1996-2000 and 2001-2003, respectively. The apparent uptake of nitrogen from soil layers was calculated from the changes of N min content between sampling terms. Most of available mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…The notion is supported by a similar, extensive utilization of available N min supply in N0 and N1 treatments (Haberle et al 2006). Thus, the roots were stimulated to growth to a deep subsoil like in N0 treatment.…”
Section: The Effect Of N Fertilization and The Year On Root Length DImentioning
confidence: 80%
See 1 more Smart Citation
“…The notion is supported by a similar, extensive utilization of available N min supply in N0 and N1 treatments (Haberle et al 2006). Thus, the roots were stimulated to growth to a deep subsoil like in N0 treatment.…”
Section: The Effect Of N Fertilization and The Year On Root Length DImentioning
confidence: 80%
“…The cultivars belong to the same grain quality group (A), both exhibit a good spring regeneration, tillering, plasticity and yield stability; cultivar Nela is by 10 cm shorter (85 cm) than Samanta (95 cm). The content of mineral N (N min = N-NO 3 -+ N-NH 4 + ), soil moisture, crop growth and nitrogen uptake were determined several times during the growth in the experiment , Haberle et al 2002, Haberle et al 2006.…”
Section: Methodsmentioning
confidence: 99%
“…The optimal response of NUE and yield was found at lower fertilizer rates (approximately 150-200 kg N/ha), with the exception of the vegetation period 2002/03 where unfavourable climatic conditions and water deficit influenced winter wheat to have a very low response to applied N. Jing et al (2009) reported that N uptake by wheat increased with increasing N rates, while agronomic NUE (kg grain/kg N applied) declined at rates exceeding 150 kg N/ha. As investigated by Haberle et al (2006), lower doses of applied N (100 kg N/ha) were crucial for achieving almost full depletion of available mineral N by winter wheat uptake in the soil up to the depth of 90 cm during the most of the vegetation period.…”
Section: Resultsmentioning
confidence: 99%
“…In well N-managed fields, resources of subsoil N are efficiently exploited by seed crops (Haberle et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In spite of that, there is a deep gap in knowledge about resources of easily available nutrients in the subsoil. The importance of the subsoil N for crops, for example for wheat, is well recognized (Haberle et al 2006). Kuhlmann (1990) based on data from 34 field experiments in Germany showed that the subsoil was responsible for 34% K supply to spring wheat.…”
mentioning
confidence: 99%